A HUBUNGAN TEKNOLOGI DENGAN KEPUASAN PENGGUNA SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) DI RSUD PANDAN ARANG KABUPATEN BOYOLALI - Wilda Rafika Rahma; Sri Sugiarsi; Sri Mulyono (Indonesian Journal of Health Information Management, 2026)
The Hospital Management Information System (SIMRS) is a computer-based application designed tomanage all medical record data. The purpose of this study was to determine the relationship betweentechnology (system quality, information quality, and service quality) with SIMRS user satisfactionusing the HOT-Fit method. The research design used analytic observational research with a cross-sectional approach and product moment correlation test to determine the relationship between eachvariable. The results showed that there was a significant relationship between system quality technologyand user satisfaction (P-Value 0.00) which had a positive meaning and was strong with a value of 0.665.There is a relationship between technology and information quality with significant user satisfaction (P-Value 0.00) which has a positive meaning and is strong with a value of 0.732. And there is a significantrelationship between service quality technology and user satisfaction (P-Value 0.00) which is positiveand strong with a value of 0.0836.